The Arab Spring, A Setback for Gender Equality? Evidence from the Gallup World Poll - Rudolf, Robert; Wang, Shun; Wu, Fengyu (KDI School of Public Policy and Management, 2020)
Combining a unique dataset from the Gallup World Poll for the period 2009 to 2018 with Wolfsfeld et al.’s (2013) protest index, we evaluate the impact of the Arab Spring pro-democracy protests on gender equality in the Middle East and North Africa. Following a double- and triple-difference approach, we find that protests significantly reduced female labor force participation as well as support for women’s rights. In particular, a one-standard-deviation increase in the protest intensity lowered female participation rates by 3.7 percentage points. Likewise, Arab Spring protests significantly lowered support for women’s legal rights, occupational rights, and divorce rights. Our results are robust to different samples, alternative model specifications, and omitted variable bias. They are also confirmed when using an alternative protest measure from Steinert-Threlkeld (2017). Regarding potential mechanisms, we suggest that a shift in the Arab zeitgeist towards a less secular society can help explain our findings.
Keywords: Arab Spring; Protests; Gender Norms; Female Labor Force Participation; Women’s Rights; Middle East and North Africa